Managing in the information society : - Masuda, Yoneji (Basil Blackwell, 1990)
This book likens the impact of Information Technology on the world of business to the way in which steam power in the last century opened up new geographical frontiers. It charts the development of IT from the 19th century to the present day, and speculates on the changes it is likely to make in the future. It suggests that in the near future the leading industries will be information industries as opposed to manufacturing and production industries.